Preventive maintenance method based on continuous time MDP model - Ao Yinhui; Wang Cuifen (2016)
The invention discloses a preventive maintenance method based on a continuous time MDP model. The method comprises steps of data fitting, mathematical modeling of an MDP model, a system structure analysis and modeling, and model solving to obtain an optimal maintenance strategy. According to the method, all factors affecting benefits of a production line are taken into consideration; and an equipment degradation process is simulated by using a continuous time MDP model and the continuity of the degradation process is emphasized. And then the system layer structure analysis is carried out and a corresponding mathematic model is established. And an optimal maintenance strategy is obtained based on optimized simulation. On the basis of the reasonable maintenance strategy, the maintenance cost is lowered; the equipment utilization rate and the yield are improved; and thus an objective of production benefit maximization is achieved. 本发明公开了种基于连续时间MDP模型的预防性维护方法。该方法包括：数据拟合、MDP模型数学建模、系统结构分析与建模、求解模型获得最佳维护策略。该方法综合考虑了影响生